Declaring Racism a Public Health Crisis in the United States: Cure, Poison, or Both? - Paine, Lilliann; de la Rocha, Patanjali; Eyssallenne, Antonia P.; Andrews, Courtni Alexis; Loo, Leanne; Jones, Camara Phyllis; Collins, Anne Marie; Morse, Michelle (Frontiers in Public Health, 2021)
Declaring racism a public health crisis has the potential to shepherd meaningful anti-racism policy forward and bridge long standing divisions between policy-makers, community organizers, healers, and public health practitioners. At their best, the declarations are a first step to address long standing inaction in the face of need. At their worst, the declarations poison or sedate grassroots momentum towards anti-racism structural change by delivering politicians unearned publicity and slowing progress on health equity (2). Declaring racism as a public health crisis is a tool that must be used with clarity and caution in order to maximize impact. Key to holding public institutions accountable for creating declarations is the direct involvement of Black and Indigenous People of Color (BIPOC) led groups and organizers. Sharing power, centering their voices and working in tandem, these collaborations ensure that declarations push for change from the lens of those most impacted and authentically engage with the demands of communities and their legacies (3). Superficial diversity and inclusion efforts that bring BIPOC people and organizers into the conversation and then fail to implement their ideas repeat historical patterns of harm, stall momentum for structural change at best, and poison the strategy at worst. In this paper we will examine three declarations in the United States and analyze them utilizing evaluative criteria aligned with health equity and anti-racism practices. Finally, we offer recommendations to inform anti-racist public health work for meaningful systematic change toward decentralization and empowerment of communities in their health futures (4).